Modelagem hidrodinâmica da circulação sobre a plataforma continental do Ceará - Brasil - Freitas, Pedro Paulo de (2015)
We aim to understand the spatial and temporal variability of the circulation on the PCCE and its main forcing using the Regional Ocean System (ROMS). We performed 10 years of simulation using 20 vertical sigma levels. We used two experiments: PCCE-1 forced only by tides and PCCE-2 forced with tides, winds, and water and heat fluxes. We used historical data and published results to validate the model. Our simulations were able to reproduce the spatial and temporal variability of the circulation within the PCCE. The tidal residual circulation presents a well-defined circulation during ebb and flood tides, with maximum values (2.0 cm/s) occurring during flood spring tides.The wind-forced circulation presents a well-defined seasonality with maximum values occurring during the second half of the year. The circulation within the PCCE is dominated by tidal zonal currents. Tides explain 87.6% and 98% of the total variability of the cross-shore currents during first and second half of the year, respectively, and 45.2% and 38% of the along-shore currents. For the first time a counterclockwise eddie is reported around thePlatô do Ceará, with velocities between and 0.2 a 0.4 m/s. Due to the larger discharge the influence of the main rivers of the PCCE is more evident during the first half of the year. During the first half of the year the presence of the Tropical Water is present at the external shelf a possible influence of the North Brazil Current. These results are supported by the diagnostics results from the model, were the dynamical balance of the external and middle shelf are dominated by the advective terms of the motion equation. The present work is any important contribution to the knowledge of the PCCE circulation. For the first time, a baroclinic model has been used to study the sazonality of the circulation and the thermal structure of the PCCE. We also studied the spatial variability of the residual tidal circulation and dynamical balance of the PCCE.